WRIPUB 2021
DOI: 10.46830/wriwp.19.00090
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Social Equity in Climate Action: Untapped Opportunities and Building Blocks for Leaving No One Behind

Abstract: Lower-income and disadvantaged people, who suffer the most from climate change and pollution, can benefit most from protection and clean solutions but face the greatest barriers to access the gains of climate policies and are disproportionately affected by their cost. Like any other policy, climate actions are designed in the context of socioeconomic and power structures that produce inequality. A just transition and the promise to “leave no one behind” require moving beyond a mere focus on social co-benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 156 publications
0
2
0
Order By: Relevance
“…Substantial investments and equity-focused innovations can provide significant advantages to these communities, such as improved healthcare, affordable energy, transportation, decent jobs, and participation in public life. However, these communities often suffer injustices, contributing less to greenhouse gas emissions but being more affected by climate change and less benefited by climate action, as well as facing higher social costs (Bouyé & Waskow, 2021).…”
Section: Inclusion and Empowerment Policiesmentioning
confidence: 99%
“…Substantial investments and equity-focused innovations can provide significant advantages to these communities, such as improved healthcare, affordable energy, transportation, decent jobs, and participation in public life. However, these communities often suffer injustices, contributing less to greenhouse gas emissions but being more affected by climate change and less benefited by climate action, as well as facing higher social costs (Bouyé & Waskow, 2021).…”
Section: Inclusion and Empowerment Policiesmentioning
confidence: 99%
“…The Egyptian strategy focuses on the alleviation and adaptation of the effects of climate change on the poor, economic growth and most vulnerable areas, whereas the Australian strategy seeks to achieve effective adaptation and enhance resilience through collaboration to drive actions, enable investments, and improve climate services and information over time. Bouyé et al (2020) conducted a broad literature review and investigated climate policies to analyze the social impact of internationally agreed commitments of climate actions. They indicated that in addition to the decision-making engagement ability of diverse groups, especially in an inequality context, climate policies with an equity-focused approach usually care about costs and benefits distribution among social groups.…”
Section: Literature Reviewmentioning
confidence: 99%